GLOBAL CLIMATE CHANGING AND ITS AFTER-EFFECTS - Lydia V. Bondarenko; Olga V. Maslova; Anastasia V. Belkina; Ksenia V. Sukhareva (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the acute issues of global climate change, which today is one of the most burning problems of the world. Analysis of different sources dealing with climate changes in the second half of the 20-th and early 21st centuries conducted by the authors gave them an opportunity to identify problems of ecological nature influencing climate changes. They grounded topicality of problems of global and regional environment and climate changes due to increasing impact of anthropogenic factors, including the continuous growth in concentration of CO2 and other green house gases in the atmosphere. The authors underline topicality of researching different effects of climate change, which could be harmful and at the same time become catalysts of various changes in many industries of economy. The article analyzes different points of view on the process of climate change, its forecast and consequences. Risks of disasters in technological and social spheres caused by global warming were demonstrated. Possible effects of global warming on the territory of Russia were shown, including those in the Arctic zone. Climatic policy and the Climatic Doctrine of the Russian Federation for the period up to 2020 were discussed. Participation of Russia in the system of global management of climate changes was underlined.